Hail potential in Europe based on a regional climate model hindcast. Issue 24 (19th December 2015) - Mohr, S.; Kunz, M.; Geyer, B.
Abstract: Due to the local‐scale nature of hail and a lack of appropriate observation systems, comprehensive, reliable, and consistent information about hail frequency and intensity in Europe is not available. To overcome this constraint, we developed a logistic hail model that quantifies the potential of the atmosphere to form hailstorms. The model is based on a combination of appropriate hail‐relevant meteorological parameters. This paper presents the application of an adjusted version of the logistic model with the objective being to estimate the hail potential across Europe based on dynamically downscaled National Centers for Environmental Prediction/National Center for Atmospheric Research1 reanalysis over a long‐term period of 60 years (1951–2010). The model output, in terms of the potential hail index (PHI), identified several hot spots that are well known from other observational studies. Time series of the PHI over the 60 year period show a high correlation at different sites across Europe and high annual and multiannual variability, but no overall trend. Key Points: Based on a logistic hail model, well‐known hail hot spots can be identified in Europe The hail potential shows large annual and multiannual variability but no overall trend Conditions that favor hailstorms are controlled by large‐scale circulation patterns and mechanisms